Treatment Protocol of Lumbar Disc Herniation with Tuina Combined with Yijinjing Based on Expert Survey - GUO Lei; WANG Cheng; ZHOU Xin; TIAN Yukui; BAI Xue; ZHU Qingguang; FANG Min; LIU Junchang (康复学报)
ObjectiveTo construct a clinical protocol for the intervention of lumbar disc herniation （LDH） with Tuina combined with Yi Jin Jing based on expert questionnaire survey.MethodsAn expert consultation questionnaire was developed based on literature research. The Delphi method was used to conduct two rounds of expert consultations on the clinical protocol for the intervention of LDH with Tuina combined with Yi Jin Jing. The enthusiasm and authority of experts were analyzed through indicators such as questionnaire recovery rate and expert authority coefficient （Cr）. The concentration of expert opinions on the indicator system was analyzed through the mean （M），standard deviation （S），and full-mark ratio （K） of the items. The coefficient of variation （CV） and Kendall's harmony coefficient （Kendall's W） were used to evaluate the variation degree of expert scores and the coordination and consistency of evaluation opinions. The clinical protocol was constructed using a composite decision-making mechanism：① indicators that simultaneously satisfy the conditions of mean <4 points，K<0.8，and CV>0.25 were deleted; ② other deletion opinions proposed by experts in the remarks were discussed and deleted after discussion between the research team and the experts. Finally，a clinical protocol integrating Tuina and Yi Jin Jing for the intervention of LDH was formed. ResultsExpert consultation data showed a 100% questionnaire recovery rate in both rounds; the expert authority coefficients were 0.73 and 0.82，respectively. The final M values of the items in the two rounds of questionnaires ranged from 4.42 to 4.87，with K values ranging from 0.54 to 0.88 and CV values ranging from 0.07 to 0.16. Kendall's W increased from 0.331 and 0.567 in the first round to 0.504 and 0.695 in the second round. After integration，the final protocol was confirmed：the clinical protocol for the intervention of LDH with Tuina combined with Yi Jin Jing requires the physician to maintain mental focus during Tuina and perform holistic treatment on the waist，hips，and buttocks; Yi Jin Jing should focus on practicing five core movements，including holding the heavens with palms，pulling nine cow tails backwards，pulling nine horse knives like a ghost，grasping with the dragon's claw，and pouncing like a tiger at least once a day，10-15 minutes each time，for 4 weeks. Practice should be combined with breath adjustment，mind adjustment，and heart adjustment. ConclusionThe clinical protocol for the intervention of LDH with Tuina combined with Yi Jin Jing provides a reference for clinical standardized treatment of LDH.